2023
DOI: 10.7759/cureus.43386
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Grouping and Rhesus Factor Determination From Dental Pulp Tissue: A Forensic Research

Moumalini Das,
Abhishek Banerjee,
Jaydeep Samanta
et al.

Abstract: Introduction Collection of blood samples from mass disaster victims and blood grouping is a challenging task. This can be attributed to various reasons. From the forensic odontology perspective, teeth and bones are one of the noteworthy remains that can be derived from such sites. Aims and objectives The aim of our study is to detect ABO blood groups and Rhesus (Rh) factor from extirpated pulp tissue of the extracted teeth at zero, three, and six months’ time interval by absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…Blood group antigens are always present in tooth pulp because of their extensive vascularity. Therefore, it is not too difficult to determine a person's blood type from pulp [20]. Our findings validated this, as the identification of ABO blood types and Rhesus factor antigen from pulpal tissue had an overall accuracy ranging from 42 (93.33%) to 44 (97.78%), whereas dentin samples exhibited an accuracy rate ranging from 35 (77.28%) to 37 (82.22%).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Blood group antigens are always present in tooth pulp because of their extensive vascularity. Therefore, it is not too difficult to determine a person's blood type from pulp [20]. Our findings validated this, as the identification of ABO blood types and Rhesus factor antigen from pulpal tissue had an overall accuracy ranging from 42 (93.33%) to 44 (97.78%), whereas dentin samples exhibited an accuracy rate ranging from 35 (77.28%) to 37 (82.22%).…”
Section: Discussionsupporting
confidence: 78%
“…In several similar studies by Ramnarayan et al [20], Shetty and Premalatha [16], and Smeets et al [22] at various periods, pulp was shown to be better than dentin, and the sensitivity of the dentin and pulp decreased with the increase in periods. The most prominent current idea posits that infusion sedimentation phenomena, in conjunction with an intrinsically existent antigen, is the source of blood-type antigens in tooth-hard tissue.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Antigens belonging to the ABO blood group are found on red blood cells, epithelial cells in the digestive and respiratory tracts, and endothelial cells beneath blood arteries, which are capable of producing ABH carbohydrate structures [25]. ABO blood grouping studies have been identified in the dental pulp tissue and secretor status was also noted in salivary samples [26,27]. The S protein of virions produced by individuals of type A may be adorned with A carbohydrate epitopes, while those produced by type B individuals could display B carbohydrate epitopes.…”
Section: Batool Et Al Storry Et Al and Cheng Et Al Examined The Corre...mentioning
confidence: 99%